Effect of Diabetes on Circulating Pancreatic Hormones in Pregnant Rats and Their Offspring - Iessi, I. L. [UNESP]; Sinzato, Y. K. [UNESP]; Gallego, F. Q. [UNESP]; Nielsen, J. H.; Damasceno, D. C. [UNESP] (Thieme, 2016)
The aim of the study was to investigate the role of diabetic intrauterine environment on circulating insulin, glucagon, and somatostatin levels in pregnant rats, fetuses, and offspring. Diabetes was induced in female Wistar rats by streptozotocin at birth or as adult and the animals were assigned into: control (C); mildly diabetic (MD); and severely diabetic (SD). The rats were mated and distributed into 2 subgroups: euthanasia at day 21 of pregnancy and at day 10 postpartum. Both MD and SD dams showed impaired oral glucose tolerance. SD dams had lower body weight and insulin levels compared to C and MD dams. SD fetuses presented hyperglycemia and reduction of insulin and glucagon levels compared to C and MD fetuses. SD newborns had diminished total pancreatic insulin and plasma somatostatin compared to the other groups. MD dams and fetuses had lower glucagon and somatostatin levels compared to C dams. MD offspring had maintained lower somatostatin levels to neonatal period. Diabetes causes alterations in circulating levels of pancreatic hormones in the mother and offspring.
Keywords: diabetes; glucagon; insulin; pregnancy; somatostatin; streptozotocin